The abundance and diversity of heterotrophic bacteria as a function of harvesting frequency of duckweed (Lemna minor L.) in recirculating aquaculture systems - Ardiansyah; Fotedar, Ravi (Blackwell Scientific Publishers, 2016)
Duckweed (Lemna minor L.) is a potential biofilter for nutrient removal and acts as a substrate for heterotrophic bacteria in recirculating aquaculture systems (RAS). Here, we determined the effects of harvesting frequency of duckweed on heterotrophic bacteria in RAS. Twelve independent RAS consisting of fish-rearing tank, biofilter tank and waster-collection tank were used to study the interactions between duckweed harvest frequencies up to 6 days and the composition, abundance and diversity of heterotrophic bacteria. After 36 days, heterotrophic bacteria in the biofilter tank were primarily Gram-negative cocci or ovoid, coccobacilli, Gram-negative cabilli and Gram-positinve bacilli. Most bacterial genera were Bacillus and Pseudomonas while the least common was Acinetobacter. Duckweed harvested after every 2 days produced the highest specific growth rates (SGR) and total harvested biomass of duckweed, but harboured less abundant bacteria, whereas 6-day harvests had a higher growth index (GI) of duckweed than 2-day harvests, but caused a poor relationship between SGR and biomass harvest with the abundance and diversity of heterotrophic bacteria. Stronger correlations (R2 > 0.65) between duckweed SGR and biomass harvest with the heterotrophic bacteria diversity were observed at 4-day harvest frequency and the control.